Disease Prediction: Prediction of Chronic Inflammation for Inhaled Particles: the Impact of Material Cycling and Quarantining in the Lung Epithelium (Adv. Mater. 47/2020). Issue 47 (24th November 2020) - Kokot, Hana; Kokot, Boštjan; Sebastijanović, Aleksandar; Voss, Carola; Podlipec, Rok; Zawilska, Patrycja; Berthing, Trine; Ballester‐López, Carolina; Danielsen, Pernille Høgh; Contini, Claudia; Ivanov, Mikhail; Krišelj, Ana; et al.
Abstract : The prediction of diseases associated with nanomaterials is currently hampered by an incomplete understanding of the underlying mechanisms. Newly discovered nanomaterial quarantining and counteracting nanomaterial cycling fill that gap allowing Tilen Koklič, Tobias Stoeger, Janez Štrancar, and co‐workers to incorporate these main modes of cellular response into a mechanistic model and predict in vivo inflammation solely on animal‐free in vitro tests, as described in article number 2003913 .